Diplomacia transfronteriza en tiempos de revolución: el Alto Río Negro iberoamericano, 1815-1820 (Estudios) - Brito, Adilson, J. I. (2015)
This article studies the impacts of the independence war in the regional border of the High Negro River, taking as it’s object of analysis the existing multiples connections between the inhabitants of both sides of the imaginary boundary line. From July 1817, the independence war in Venezuela changed the coordinates: the struggles between the republican patriots and those obedient to the King (Realistas), faithful to the restoration of the Spanish monarchy of Fernando VII, managed the great border region, and influenced the political, social and local dynamics, mainly the existing cross-border relations between both, impacted the ordinary life of the local population and affected the diplomacy between the Portuguese and Spanish American authorities, those faithful to the King (Realistas) and patriots.